Successful treatment with eculizumab in a patient with pregnancy-associated atypical hemolytic uremic syndrome. (June 2023) - Duran, Mehmet Nuri; Beyazit, Fatma; Erbaş, Mesut; Özkavak, Onur; Acar, Celal; Bakirdogen, Serkan
Pregnancy‐associated atypical haemolytic uraemic syndrome is a rare and potentially lethal complement-mediated disorder. It can mimic preeclampsia, gestational hypertension, thrombotic thrombocytopenic purpura and hemolysis, elevated liver enzymes and low platelets syndrome. Thus, it can be hard to distinguish pregnancy‐associated atypical haemolytic uraemic syndrome from other causes in peri/post-partum women presenting with features of microangiopathic haemolytic anemia, thrombocytopenia and acute kidney injury. We present a case of a 35-year-old woman in her third pregnancy at 32 weeks' gestation who underwent caesarean section due to fetal distress. She developed severe renal impairment, thrombocytopenia and neurologic symptoms within 24 hours after delivery. A diagnosis of pregnancy‐associated atypical haemolytic uraemic syndrome was provided, and treatment with plasma therapy followed by eculizumab was initiated. A rapid improvement of both clinical and laboratory parameters was observed. This case demonstrates the significance of early initiation of anti-complement therapy to prevent irreversible renal damage and possible death in women with pregnancy‐associated atypical haemolytic uraemic syndrome.